O problema do outro em Sartre - Gonçalves, Aline Ibaldo (2012)
Through the look starts the relationship with the Other. In Being and Nothingness, Sartre uses the example of shame as a way of being of consciousness which the other arises as a mediator of The Self with itself, because I feel ashamed of myself as I appear to the others. There is a connection between me and the other, different from my relationship with objects. When I am seen, I'm aware of me, but I am not my own foundation, I have my foundation outside myself through the others. By the look, I live the alienation of my possibilities, because the other transforms me into an object. By being objectified, I get an externality as if I had an essence. But man does not have access to this essence, he is an eternal becoming, which is never complete. The existence and the freedom of others threaten me, because I stay immobilize in the being-in-itself. However, I do not coincide with what others apprehend of me, because I cannot look at me like the other looks. It will always be indecipherable to me. But, anytime I can return the other s look, thus, putting myself in my own freedom confronting the other. To proceed with the analysis of intersubjectivity, Sartre writes an ontology of the body. It s through the body that I have a relationship with the other. The body is the contingent shape of the contingency. Through the look, the body is revealed by the other as a being-in-itself and the facticity is objectified and alienated. There are two ways of concrete relations with others: attempts to assimilate the other (love, language, masochism) which we try to become owners of the freedom of others, wanting to possess it as consciousness, making me as an object to possess the other s freedom; and attempts at objectification of the other (indifference, desire, hate, sadism) which I try to take my freedom back, alienating the other, reducing him into an object. So I petrify his freedom. Both situations fail, because freedom is inalienable. If I try objectify me is through an free project and if I try to objectify the other, him as a subject escapes me, because it s not possible to possess the other as a subject, only as an object and thus, we have no access to his conscience. Sartre presents another problem: The us. That implies a plurality of subjectivities that are recognized as subjectivities. The Heidegger s Mitsein opposes the thesis of the Sartre s conflict. Sartre limits us to private consciences. The being-for-others is the foundation of being-with-others. This conflict occurred because Sartre defines man as freedom. The Human-being is an absolute freedom and he cannot share his freedom with others. The essence of the relationship between consciousnesses will always be conflict.